Removing Ethylene by Adsorption using Cobalt Oxide-Loaded Nanoporous Carbon - Imam Prasetyo; Nur Indah Fajar Mukti; Moh Fahrurrozi; Teguh Ariyanto (Department of Chemical Engineering, Universitas Gadjah Mada, 2018)
Ethylene is naturally generated by climacteric fruits and can promote the ripening process faster. For effective long-distance transport and subsequent storage, removing ethylene from the storage environment has been of interest to suppress its undesirable effect. In this study, ethylene removal by an adsorptive method using cobalt-loaded nanoporous carbon is studied. Cobalt oxide-loaded carbon was prepared by incipient wetness method followed by calcination process at 200 °C under inert flow. Ethylene adsorption test was performed at 20, 30, and 40 °C using a static volumetric test. The results showed that cobalt oxide/carbon system has significant ethylene adsorption capacity up to 3.5 times higher compared to blank carbon. A higher temperature adsorption is more favorable for this chemisorption process. Ethylene uptake increases from 100 to 150 mL g-1adsorbent STP by increasing cobalt oxide loading on carbon from 10 to 30 wt.% Co. The highest uptake capacity of 6 mmol ethylene per gram adsorbent was obtained using 30 wt.% cobalt oxide. Therefore, ethylene adsorption by cobalt-loaded nanoporous carbon may represent a potential method in ethylene removal and it could serve as a basis for development of ethylene scavenging material.